Genetic risk scores and number of autoantibodies in patients with rheumatoid arthritis. Issue 4 (13th December 2013) - Maehlen, Marthe T; Olsen, Inge C; Andreassen, Bettina K; Viken, Marte K; Jiang, Xia; Alfredsson, Lars; Källberg, Henrik; Brynedal, Boel; Kurreeman, Fina; Daha, Nina; Toes, Rene; Zhernakova, Alexandra; et al.
Abstract : Objective: Certain HLA-DRB1 alleles and single-nucleotide polymorphisms (SNPs) are associated with rheumatoid arthritis (RA). Our objective was to examine the combined effect of these associated variants, calculated as a cumulative genetic risk score (GRS) on RA predisposition, as well as the number of autoantibodies (none, one or two present). Method: We calculated four GRSs in 4956 patients and 4983 controls from four European countries. All four scores contained data on 22 non-HLA-risk SNPs, and three scores also contained HLA-DRB1 genotypes but had different HLA typing resolution. Most patients had data on both rheumatoid factor (RF) and anti-citrullinated proteins antibodies (ACPA). The GRSs were standardised (std.GRS) to account for population heterogeneity. Discrimination between patients and controls was examined by receiveroperating characteristics curves, and the four std.GRSs were compared across subgroups according to autoantibody status. Results: The std.GRS improved its discriminatory ability between patients and controls when HLA-DRB1 data of higher resolution were added to the combined score. Patients had higher mean std.GRS than controls (p=7.9×10 −156 ), and this score was significantly higher in patients with autoantibodies (shown for both RF and ACPA). Mean std.GRS was also higher in those with two versus one autoantibody (p=3.7×10 −23 ) but was similar in patients without autoantibodies and controls (p=0.12). Conclusions: The GRS was associated with the number of autoantibodies and to both RF and ACPA positivity. ACPA play a more important role than RF with regards to the genetic risk profile, but stratification of patients according to both RF and ACPA may optimise future genetic studies.